Research on the Path of Legal Protection of Artificial Intelligence - Zhang, Zezhong (International Journal of Social Sciences and Public Administration, 2024)
The rule of law of artificial intelligence industry depends on the coordination and cooperation of soft law guarantee path and hard law guarantee path. Compared with Western countries, China's artificial intelligence industry developed late, and its legislation mainly has some problems, such as insufficient power of soft law generation mechanism, fuzzy norms of hard law and fuzzy judgment standards of dispute settlement mechanism. This paper believes that China can learn from the legislative experience of European and American countries to implement graded assessment of artificial intelligence risks, and define the judgment criteria; Secondly, our country can draw on the soft law documents such as resolutions of international organizations as the basis of soft law generation; In terms of dispute settlement mechanism, China can try to use the "Maple Bridge experience" to introduce artificial intelligence dispute cases.